Influence of secondary electron emission on the RF gas breakdown - Dakhov, A.N.; Dudin, S.V. (Вопросы атомной науки и техники, 2013)
The influence of the electron impact secondary electron emission on the RF gas breakdown has been researched experimentally and theoretically with use of particle-in-sell simulation. The experiments and simulations are conducted in the discharge chamber with asymmetric electrodes which is frequently used in technological applications. As a result, the physical mechanism of secondary electron participation in the RF breakdown has been revealed.